Satisfying and delighting the rural tourists - Loureiro, S. M. C. (Journal of Travel and Tourism Marketing, 2010)
This study applies the concept of customer delight and the model proposed by Oliver, Rust, and Varki (1997) and modified by Finn (2005) to the context of rural tourism. The model is applied to rural tourism lodgings in northern Portugal and validated using PLS technique. The results suggest that satisfaction is a more significant determinant of loyalty than delight and disconfirmation is an important predictor of both satisfaction and delight. This study further supports the conceptualization of customer delight and customer satisfaction as distinct constructs. Results may help managers of rural tourism accommodations to develop and implement more successful relationship marketing strategies.